PROGRAM RUTIN PEMERIKSAAN PERKEMBANGAN ANAK DENGAN MENGGUNAKAN ALAT DDST II - Lailatulrohmah, Lailaturohmah (Jurnal LENTERA, 2024)
Child development assessment is a crucial step in ensuring optimal growth in the early stages of life. The Denver Developmental Screening Test (DDST) II, as a clinically proven structured instrument, serves as a vital tool for early detection of potential developmental issues in children.. This community service aims to increase awareness and understanding among the community regarding early detection of child development through the implementation of a Routine Child Development Assessment Program using the Denver Developmental Screening Test (DDST) II. The service was conducted at Daycare Al-Amiin, involving 20 children aged 2-3 years as participants. The service method includes assessments using the DDST II tool, evaluating psychomotor, language, and socio-emotional development in 20 children. The results show that out of the 20 children assessed, 18 exhibited normal development, while 2 showed signs of developmental tendencies requiring further attention (suspect). This data provides a positive overview of the program's effectiveness in early detection of potential developmental issues. Increased community awareness is evident from the active participation of daycare managers in these routine activities.